Olympic Games in the 'agenda-setting' of the modern media: The role of social networks in communicating information to the audience - R.P. Bakanov; V.S. Mayorov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper presents the results of the study of the role of social networks in obtaining information by journalists and bringing it to the audience. Using the methods of comparative, substantive, and functional analysis, it has been studied how the Olympic Games are covered by social networks based on the leading Russian and international media. The functional features of social networks have been identified. The examples of how they are integrated into the work of journalists have been provided. The problems that journalists may face when working with social networks have been described. The problems experienced by modern sports media in the absence of cooperation with social networks. It has been pointed out how the media content is formed when social networks are used, as well as how these social networks affect the number of audiences in these works. According to the results of the study, it has been suggested that social networks contribute significantly to the work of journalists. The conclusion has been made that the coverage of the Olympic Games in social networks can be called acceptable, but journalists have not yet used the full potential of social networks.